Arduino Based Distancing Wristband Design - Sujono Sujono; Aji Setyo Hartono Prawoto (NEWTON: Networking and Information Technology, 2022)
Covid disease is a very dangerous disease because this disease is very easily transmitted to everyone, from the young to the elderly. With the conditions that are maintained and in this pandemic situation, many people underestimate how material the Covid 19 virus is. In designing this system simulation model, the devices used are in the form of a mini Arduino, pear sensor, battery, and buzzer. The method used to maintain a safe distance from people affected by Covid 19. In the form of research that can test how important it is for us to keep our distance from other people. With Arduino technology and pear sensors used to remind us that the distance between humans. So we have to be a bit oblivious when there is an output from the buzzer which has been warned by the pir sensor. With this tool, we can at least keep a distance from people around us